Treating benign paroxysmal positional vertigo of the lateral semicircular canal with a shortened forced position - Giannoni, Beatrice; Pecci, Rudi; Pollastri, Federica; Mininni, Sebastiano; Licci, Giuseppe; Santimone, Rossana; Di Giustino, Fabio; Mandalà, Marco (Frontiers in Neurology, 2023)
Benign Paroxysmal Positional Vertigo (BPPV) is the peripheral vestibular disorder most frequently encountered in routine neuro-otological practice. Among the three semicircular canals, the lateral one (LSC) is the second most frequently interested by the pathological process. In most cases LSC BPPV is attributable to a canalo- or cupulothiasis mechanism. The clinical picture is that of a positional nystagmus and vertigo evoked by turning the head from the supine to the side lateral positions. With such a movement a horizontal positional (and often also paroxysmal) direction-changing nystagmus is generated. Depending on whether the pathogenetic mechanism is that of a canalo- or cupulolithiasis and on where the dense particles are, LSC BPPV direction changing positional nystagmus is geotropic or apogeotropic on both lateral sides. Due to its mechanical nature, BPPV is effectively treated by means of a physical therapy. In the case of a LSC BPPV, one the most effective therapies is the Forced Prolonged Position (FPP), in which the patient is invited to lie 12 hours on the lateral side on which vertigo and nystagmus are less intense, in order to move the canaliths out from the canal (or to shift them inside of the canal from a tract to another) exploiting the force of gravity. Despite its efficacy, FPP is not always well tolerated by every patient and it cannot be done during the diagnostic session because of its duration. The aim of this work was to verify the efficacy of a different forced position, shortened (SFP) with respect to the original, so that patients could bear it better and physicians could control the outcome almost immediately, possibly dismissing patients without vertigo. After one hour lying on the side where vertigo and nystagmus are least, 38/53 (71.7%) patients treated with SFP were healed or improved. Though outcomes are not as satisfying as those of original FPP, SFP should be considered as a therapeutic chance especially by those physicians who work in collaborating with emergency departments or facing otherwise acute patients in order to resign patients without vertigo, as soon as possible.